Cost-Benefit Analysis of IoT-Enhanced Maintenance: A Quantitative Assessment for Large-Format Printing Machine (INTERNATIONAL JOURNAL OF INDUSTRIAL AND PRODUCTION ENGINEERING, 2024)
This paper offers a compelling cost-benefit analysis of implementing Internet of Things (IoT)-enhanced maintenance strategies for large-format printing machines, with a focus on the Yinghe 6-feet printer. By comparing pre-IoT (January 2021 to December 2022) and post-IoT (January to July 2023) data, the study demonstrates significant reductions in maintenance frequency, technician labor costs, and machine component replacement expenses. Notably, the IoT system effectively minimizes wasted flex material and improves ink efficiency. Key findings include a 49.4% reduction in average monthly technician labor costs, a 93.9% reduction in average monthly machine component replacement costs, and an 87.6% reduction in wasted flex material. These findings have profound implications for industries relying on large-format printing machines, showcasing the potential for cost savings, increased efficiency, and extended equipment lifespan through IoT adoption. The paper concludes with a strong recommendation for organizations to consider IoT-enhanced maintenance strategies based on the observed empirical evidence, contributing invaluable insights to the optimization of maintenance practices in industrial settings.
Keywords: IOT; MAINTENANCE; COST; BENEFIT